The Nordic Council and European co-operation : report of the Nordic Council's Committee on International Co-operation - Pohjoismaiden neuvosto (NU-[serien], ISSN 0349-8328, 1989)
Summary (s. 7-10).
Keywords: Pohjoismaiden neuvosto; pohjoismainen yhteistyö; kansainvälinen yhteistyö